A Comparative Study of Physiological and Physical Variables of Hockey and Football Players of Gujarat - Avinashkumar B Solanki; Dr Bharat Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This study aims to compare the physiological and physical variables of hockey and football players from Gujarat. Through a series of tests, this research evaluates key parameters such as aerobic capacity, muscular strength, endurance, agility, and recovery rates. The goal is to understand how these variables differ between the two groups and how they correlate with athletic performance in their respective sports. The study found significant differences in aerobic endurance and recovery time between hockey and football players, with football players exhibiting greater strength and power. These findings contribute to the understanding of how training and sport-specific demands influence the physical and physiological traits of athletes. This research will help inform tailored training programs for players in both sports to enhance performance.
Keywords: Hockey; Football; Physiological Variables; Physical Variables; Gujarat; Aerobic Capacity; Endurance; Muscular Strength; Agility; Performance